Mechanical Control of Nanomaterials and Nanosystems - Ariga, Katsuhiko; Mori, Taizo; Hill, Jonathan P. (Advanced materials (Weinheim), 2012)
In situations of power outage or shortage, such as periods just following a seismic disaster, the only reliable power source available is the most fundamental of forces i.e., manual mechanical stimuli. Although there are many macroscopic mechanical tools, mechanical control of nanomaterials and nanosystems has not been an easy subject to develop even by using advanced nanotechnological concepts. However, this challenge has now become a hot topic and many new ideas and strategies have been proposed recently. This report summarizes recent research examples of mechanical control of nanomaterials and nanosystems. Creation of macroscopic mechanical outputs by efficient accumulation of molecular‐level phenomena is first briefly introduced. We will then introduce the main subject: control of molecular systems by macroscopic mechanical stimuli. The research described is categorized according to the respective areas of mechanical control of molecular structure, molecular orientation, molecular interaction including cleavage and healing, and biological and micron‐level phenomena. Finally, we will introduce two more advanced approaches, namely, mechanical strategies for microdevice fabrication and mechanical control of molecular machines. As mechanical forces are much more reliable and widely applicable than other stimuli, we believe that development of mechanically responsive nanomaterials and nanosystems will make a significant contribution to fundamental improvements in our lifestyles and help to maintain and stabilize our society. This Progress Report summarizes examples on mechanical control of nanomaterials and nanosystems and mainly focuses on recent research in this field. Approaches to create macroscopic mechanical outputs upon accumulation of molecular‐level phenomena and controls of molecular systems by macroscopic mechanical stimuli are described. As mechanical forces are much reliable and widely applicable, we believe these efforts have significant contributions for improving our life.